2018
DOI: 10.1002/cpt.1020
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐Specific Variant Classifier (DPYD‐Varifier) to Identify Deleterious Alleles of Dihydropyrimidine Dehydrogenase

Abstract: Deleterious variants in dihydropyrimidine dehydrogenase (DPD, DPYD gene) can be highly predictive of clinical toxicity to the widely prescribed chemotherapeutic 5-fluorouracil (5-FU). However, there are very limited data pertaining to the functional consequences of the >450 reported no-synonymous DPYD variants. We developed a DPYD-specific variant classifier (DPYD-Varifier) using machine learning and in vitro functional data for 156 missense DPYD variants. The developed model showed 85% accuracy and outperform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 38 publications
4
66
0
Order By: Relevance
“…An extensive search of genetic variants of DPYD associated with enzyme deficiency and poor-metabolizer status has been performed and several genotypes were identified [5, 8, 22]. In agreement with three meta-analyses [10, 23, 24], our study confirmed the well-known role of c.1905+1G>A and c.2846A>T in fluoropyrimidine-associated ADRs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An extensive search of genetic variants of DPYD associated with enzyme deficiency and poor-metabolizer status has been performed and several genotypes were identified [5, 8, 22]. In agreement with three meta-analyses [10, 23, 24], our study confirmed the well-known role of c.1905+1G>A and c.2846A>T in fluoropyrimidine-associated ADRs.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the c.2194A allele seems to be relatively common, conflicting results have been reported concerning its influence on DPD activity and association with clinically-relevant ADRs. Some studies did not assign a role to c.2194G>A in the occurrence of fluoropyrimidine toxicity [32, 33] and in silico analysis demonstrated a normal enzyme activity [8]. A study found that c.2194G>A showed weak evidence for association with reduced DPD activity in African-American patients; c.2194GA patients displayed a 29% reduction in DPD activity compared to the wild-type, although the linkage with c.557A>G (p.Y186C) may have played a prominent role [34].…”
Section: Discussionmentioning
confidence: 99%
“…nl/shared/genes/DPYD. However, in order for these variants to be included in Table 1, sufficient evidence regarding the effect on enzyme function or the onset of toxicity must be investigated, possibly by using the DPYD-Varifier [19] or by phenotyping patients who carry a novel variant. An update of this guideline will be published when a renewed recommendation is given following newly published articles.…”
Section: Dpyd Variants Associated With Toxicitymentioning
confidence: 99%
“…3 This discrepancy is unsurprising as genotyping DPYD has been repeatedly characterized as being highly specific but with a poor sensitivity, thus possibly underestimating the actual incidence of DPD deficiency. 31 Consequently, and despite the continuous efforts to better understand the impact of new deleterious variants in DPYD 32 or to develop genetic scores to customize 5-FU dose, 33 preemptive genotyping remains unrecognized by both the European Society for Medical Oncology 34 and the US National Comprehensive Cancer Network panel. 35 Patients with U > 150 ng/ml should be precluded for any fluoropyrimidine-based therapy.…”
Section: Discussionmentioning
confidence: 99%